2012
DOI: 10.1097/npt.0b013e318262e5ab
|View full text |Cite
|
Sign up to set email alerts
|

Life Care Planning Projections for Individuals With Motor Incomplete Spinal Cord Injury Before and After Locomotor Training Intervention

Abstract: The lifetime financial costs associated with equipment, home renovations, and transportation following a motor-incomplete SCI were decreased following an intensive LT program for the 2 cases presented in this article. The LCP, including costs of rehabilitation and long-term medical and personal care costs, may be an effective tool to discern cost benefit of rehabilitation interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Limiting our analysis to health system rehabilitation costs may be acceptable because rehabilitation is the largest cost post-SCI [ 53 ], but focusing on health system costs misses potential out of pocket costs borne by individuals and family members. Limiting the analysis to one-year costs may be acceptable because there is no evidence suggesting that incremental differences exist between locomotor training strategies over the long term, though savings have been estimated for locomotor training strategies versus no training [ 54 ].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Limiting our analysis to health system rehabilitation costs may be acceptable because rehabilitation is the largest cost post-SCI [ 53 ], but focusing on health system costs misses potential out of pocket costs borne by individuals and family members. Limiting the analysis to one-year costs may be acceptable because there is no evidence suggesting that incremental differences exist between locomotor training strategies over the long term, though savings have been estimated for locomotor training strategies versus no training [ 54 ].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 87 , 88 Recent small scale studies on locomotor training with FES and robotic assistance demonstrated improvements in mental health related quality-of-life in SCI, 89 , 90 and likewise high intensity body weight support locomotor training has also been shown to improve quality of life in people with Parkinsonism. 91 By virtue of improving walking ability, locomotor training may reduce home renovation costs by >US$50,000/person and also substantially reduce lifetime healthcare costs in more impaired individuals., 81 , 92 thus easing these patients’ overall disease burden. PwCM remain at increased risk of falls and fragility fractures, and due to their sedentary lifestyles they are also prone to developing coronary artery disease, arrhythmias, and strokes.…”
Section: Mental Health Quality Of Life and Economicsmentioning
confidence: 99%
“…Less intensive locomotor training (twice a week) also appears to be beneficial (187). Morrison et al (178,179) estimated that locomotor training reduced lifetime care costs. Two reviews (169,176) suggested that while some of these approaches show potential for ambulatory improvement, randomized clinical trials are needed to show that these instrument-intensive programs are better than progressive overground training (55).…”
Section: Importance Of Locomotor Trainingmentioning
confidence: 99%